An Update on Clinical Burden, Diagnostic Tools, and Therapeutic Options of Staphylococcus aureus. (16th May 2017) - Reddy, Prakash Narayana; Srirama, Krupanidhi; Dirisala, Vijaya R
Staphylococcus aureus is an important pathogen responsible for a variety of diseases ranging from mild skin and soft tissue infections, food poisoning to highly serious diseases such as osteomyelitis, endocarditis, and toxic shock syndrome. Proper diagnosis of pathogen and virulence factors is important for providing timely intervention in the therapy. Owing to the invasive nature of infections and the limited treatment options due to rampant spread of antibiotic-resistant strains, the trend for development of vaccines and antibody therapy is increasing at rapid rate than development of new antibiotics. In this article, we have discussed elaborately about the host-pathogen interactions, clinical burden due to S aureus infections, status of diagnostic tools, and treatment options in terms of prophylaxis and therapy.